Penambahan Madu pada Minuman Whey Kefir Ditinjau dari Mutu Organoleptik, Warna, dan Kekeruhan - Firman Jaya; Purwadi Purwadi; Wahyu Novia Widodo (Faculty of Animal Science Universitas Brawijaya, 2017)
The objective of this research was to determine the optimum honey addition on kefir whey drink based on organoleptic quality (colour, aroma, taste), colour test, and turbidity. The method used in this research was experiment with Completely Randomized Design (CDR) by used 4 treatments and 4 replications. The treatments were P0 = without the honey added, P1=added by 20% honey, P2 = added by 30% honey and P3 = added by 40% honey (v/v). The data were analyzed by Analysis of Variance (ANOVA), if there were significantly difference, the data would analyzed by Duncan’s Multiple Range Test. The results showed that honey addition gave highly difference significant (P<0.01) on organoleptic quality (colour, aroma, taste), turbidity and lightness (L*). Honey addition didn’t give significantly difference (P<0.05) on redness (a*) and yellowness (b*). The conclusion of this research was the best treatment will the value is added by 40% honey with colour 3.25±0.78, aroma 3.50±1.14, taste 3.75±1.01, lightness (L) 31.57±0.5, redness (b*) 0.95±0.12, yellowness (b*) 0.050±0.36, and turbidity 306.7±6.65 NTU